Ceftolozane/Tazobactam Treatment of Multidrug-resistant Pseudomonas aeruginosa Infections in Children. Issue 5 (May 2020) - Molloy, Leah; Abdulhamid, Ibrahim; Srivastava, Ruma; Ang, Jocelyn Y.
Abstract : The clinical use, safety and effectiveness of ceftolozane/tazobactam among 13 patients 3 months to 19 years of age infected with multidrug-resistant Pseudomonas aeruginosa are described. All but one patient achieved clinical cure after initial treatment. Adverse drug events attributed to treatment included transaminitis and neutropenia which occurred in 2 patients and resolved upon dose reduction.